Optimization of velocity characteristics of the Yurchenko vault - Hedbavny, P.; Kalichova, M. (Science of Gymnastics Journal, 2015)
Various versions of the Yurchenko vault are contemporarily the most widely used vaults in women`s gymnastics. Using a 3D kinematic analysis of the velocity characteristics, our aim was to investigate basic variants of the Yurchenko vault, their mutual relations in chosen phases and various influences on the technique of execution. 14 vaults performed by elite artistic gymnasts both from the Czech Republic and abroad were assessed, among which it was possible to observe an individual approach to handling the locomotor task displaying varying degrees of fluctuation in both the overall velocity of the COG - vabs, and its horizontal component vx as well as vertical component vz. Despite the variety, the obtained results were used to determine the optimal course of these velocity parameters, which serves as a precondition of the correct technical execution of the Yurchenko vault. Although our study deals only with the selected characteristics of the whole series of variables affecting the quality of the execution of the Yurchenko streched, we believe our new research findings may be used by coaches and their athletes in their training practice.